Some ADHD polymorphisms (in genes DAT1, DRD2, DRD3, DBH, 5-HTT) in case-control study of 100 subjects 6-10 age - Kopečková, Marta; Paclt, Ivo; Petrásek, Jan; Pacltová, Dagmar; Malíková, Marcela; Zagatová, Veronika (Neuro-endocrinology letters, 2008)
BACKGROUND: Pharmacological approach is the most effective way of treatment of ADHD and its early application prevents from the progress of secondary disorders. The study on present neurotransmitter systems in pathology of ADHD can be helpful in selecting appropriate drug, since there are used various substances with different mechanisms of functioning in treatment of the hyperkinetic syndrome.
Keywords: receptory dopaminu D3; proteiny přenášející dopamin přes plazmatickou membránu; studie případů a kontrol; Genetic Predisposition to Disease; Case-Control Studies; Humans; Child; dopamin-beta-hydroxylasa; lidé; financování organizované; receptory dopaminu D2; Polymorphism, Single Nucleotide; Dopamine Plasma Membrane Transport Proteins; dítě; frekvence genu; Receptors, Dopamine D3; Attention Deficit Disorder with Hyperactivity; Financing, Organized; DNA Mutational Analysis; Female; Receptors, Dopamine D2; rizikové faktory; Gene Frequency; Male; Risk Factors; mutační analýza DNA; Dopamine beta-Hydroxylase; Serotonin Plasma Membrane Transport Proteins; genetická predispozice k nemoci; ženské pohlaví; membránové transportní proteiny pro serotonin; mužské pohlaví; hyperkinetická porucha; jednonukleotidový polymorfismus